2017
DOI: 10.1016/j.ccell.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

A UBE2O-AMPKα2 Axis that Promotes Tumor Initiation and Progression Offers Opportunities for Therapy

Abstract: SUMMARY UBE2O is localized in the 17q25 locus, which is known to be amplified in human cancers, but its role in tumorigenesis remains undefined. Here we show that Ube2o deletion in MMTV-PyVT or TRAMP mice profoundly impairs tumor initiation, growth and metastasis, while switching off the metabolic reprogramming of tumor cells. Mechanistically, UBE2O specifically targets AMPKα2 for ubiquitination and degradation, and thereby promotes activation of the mTOR-HIF1α pathway. Notably, inactivation of AMPKα2, but not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
123
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(126 citation statements)
references
References 48 publications
(60 reference statements)
3
123
0
Order By: Relevance
“…Recent evidence shows that UBE2O is involved in adipogenesis [4], actin polymerization [25], inflammation [7], nuclear trafficking of chromatin-associated proteins [5], and tumorigenesis [6]. Different from previous findings, the present study suggests that UBE2O acts as a negative modulator in MM because it is downregulated in MM cells which was confirmed by both DNA microarray and RT-PCR.…”
Section: Discussionsupporting
confidence: 60%
“…Recent evidence shows that UBE2O is involved in adipogenesis [4], actin polymerization [25], inflammation [7], nuclear trafficking of chromatin-associated proteins [5], and tumorigenesis [6]. Different from previous findings, the present study suggests that UBE2O acts as a negative modulator in MM because it is downregulated in MM cells which was confirmed by both DNA microarray and RT-PCR.…”
Section: Discussionsupporting
confidence: 60%
“…The results of Vila et al (2017) therefore fully support the idea that AMPK-α2 is a tumor suppressor. They not only identify the first downstream target for UBE2O, but also the first ubiquitin ligase that seems to specifically target AMPK-α2 for degradation.…”
Section: Grahame Hardiesupporting
confidence: 72%
“…Consistent with this, recent analyses of the human cancer genome databases revealed that while the PRKAA2 gene (encoding α2) is quite often mutated in human cancers, PRKAA1 tends to be amplified instead (Monteverde et al, 2015;Ross et al, 2016). Vila et al (2017) were interested in the role of UBE2O, a large ubiquitin ligase with both E2 and E3 activities. UBE2O is located within a chromosomal region (17q25) that is amplified in some human cancers.…”
Section: Grahame Hardiementioning
confidence: 85%
“…Thus, for instance, MAGE (melanoma antigen genes)-A3 and MAGE-A6 proteins, which are testis-specific genes that are abnormally expressed in a variety of tumors, potently promote tumor growth by, in part, mediating the ubiquitin-dependent degradation of AMPKα1 by the TRIM28 ubiquitin ligase (Pineda et al, 2015). In addition, UBE20 (ubiquitin-conjugating enzyme E20) was similarly reported to promote tumor growth by targeting AMPKα2 for ubiquitination and degradation (Vila et al, 2017). Moreover, another ubiquitin ligase, called WWP1, was reported to degrade AMPKα2 under high-glucose conditions in muscle cells (Lee et al, 2013), suggesting that ubiquitin-dependent degradation of AMPK may be a more broad mechanism for the regulation of AMPK than is currently recognized.…”
Section: Nucleotide-dependent and Nucleotide-independent Regulation Omentioning
confidence: 99%